Care-giving behaviors and other factors affecting the nutritional status of Orang Asli children in Selangor, Malaysia - Sivapathy, Shashikala (2007)
The purpose of this study is to determine the relationship between caregiving behaviors and other factors which affect nutritional status of Temuan and Mahmeri Orang Asli children aged 1-3 and 4-6 years old in Sepang and Kuala Langat districts. This cross-sectional study was carried out among children aged 1-6 years old in Orang Asli villages in Sepang and Carey Island, Selangor. There were 173 children between the ages of 1 and six years, of these 92 children were from the age group of 1-3 years and 81 children were in the age group of 4-6 years. The care behaviours which were studied were feeding behaviours, hygiene behaviours and parental control on child feeding. Caregiving behaviour was assessed by questionnaire and qualitative method.This study revealed high prevalence of malnutrition in Orang Asli children and supports the evidence in the literature. Prevalence of significantly underweight, stunted and wasting were 53.3%, 55.4% and 8.7% respectively among children 1-3 years old whereas prevalence of significantly underweight, stunted and wasting among children 4-6 years old were 38.3%, 51.9% and 6.2% respectively. Caregiving behaviours that was associated positively with nutritional status of 1-3 years old was affectionate gestures. Behaviours that were associated negatively were shared plate and activities during feeding. Among children 4-6 years old, caregiving behaviours that were associated positively were food not prepared specifically for the child and food refusal while monitoring, negative social behaviours, and affectionate gestures were associated negatively with the nutritional status. As a conclusion, this study has shown, that there were some caregiving behaviours which have positive influence on the nutritional status of child and others which was not associated with the nutritional status of the child. Different caregiving behaviours influences differently among younger and older children. With regards to hygiene behaviours, it was not found to influence nutritional status of both age groups.